CIVIL-LEGAL FOUNDATIONS OF INSURANCE RELATIONS IN ROAD TRANSPORT LOGISTICS (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article provides a comprehensive study of the civil-legal foundations of insurance relations in road transport logistics. The institutions of cargo and carrier liability insurance, the legal nature of insurance and recourse claims, and the interrelation between insurance contracts and transport contracts are thoroughly analyzed. Based on the experience of Germany and China, the article proposes, as a scientific novelty, the substantiation of insurance mechanisms as an effective legal instrument for managing logistics risks. Specific legislative proposals aimed at improving the current legislation of Uzbekistan have been developed. Conclusions are drawn from a comparative analysis of international standards and the national legal system.
Keywords: road transport logistics, insurance relations, cargo insurance, carrier liability, recourse claim, insurance contract, transport contract, logistics risks, legal regulation, Uzbekistan legislation.